Food export restrictions during the COVID-19 pandemic: Real and potential effects on food security - Aleksandra Kowalska; Anna Budzyńska; Tomasz Białowąs (International Journal of Management and Economics, 2022)
The purpose of the article is to review and critique the implementation of food export restrictions in times of crisis in addressing food security challenges. The methodological approach was to undertake a narrative literature review to outline the challenge of ensuring food security in times of crisis. We explored the problem of food export restrictions introduced in 2007-2008 and 2020 and assessed the changes in the state of food security at the national level during the COVID-19 pandemic using the Global Food Security Index (GFSI). The trade restrictions imposed in 2020 did not play a key role in the increases in international food prices as was the case during 2007-2008 and 2010-2011. The analysis of GFSI values questions whether food export restrictions have been sufficient measures given the size of the food security challenge during the pandemic, and this is a new contribution of this research. The issue of food export restrictions is underregulated in the World Trade Organization (WTO), and this needs to be urgently addressed by another institution, e.g., Food and Agriculture Organization (FAO), given that the war in Ukraine is endangering food security across the world.
Keywords: F02; F13; Q18; 650; COVID-19; FAO food price index; food export restrictions; food security; WTO